(untitled) (Research, Society and Development, 2022)
This paper presents a methodological proposal for the teaching-learning of ecology through field activity, in the form of a script for carrying out practical work of field observations. The script was designed to guide practical classes in the field, as these are usually quite dispersive, due to the high motivation of students and the diversity of learning challenges that are provided. In order to offer the student experience situations that contribute to the construction of knowledge in ecology, this methodology was proposed, seeking to streamline and optimize the construction of knowledge. The script was applied with six class of academics from biology courses and using qualitative methods the main observations measured in the development of classes are presented and discussed.